Neutrophil adhesion to vessel walls impairs pulmonary circulation in COVID-19 pathology - Hiroshi Ueki; I-Hsuan Wang; Maki Kiso; Kenta Horie; Shun Iida; Sohtaro Mine; Michiko Ujie; Hung-Wei Hsu; Chen-Hui Henry Wu; Masaki Imai; Tadaki Suzuki; Wataru Kamitani; et al. (Nature Communications)
Abstract Microthrombus formation is associated with COVID-19 severity; however, the detailed mechanism remains unclear. In this study, we investigated mouse models with severe pneumonia caused by SARS-CoV-2 infection by using our in vivo two-photon imaging system. In the lungs of SARS-CoV-2-infected mice, increased expression of adhesion molecules in intravascular neutrophils prolonged adhesion time to the vessel wall, resulting in platelet aggregation and impaired lung perfusion. Re-analysis of scRNA-seq data from peripheral blood mononuclear cells from COVID-19 cases revealed increased expression levels of CD44 and SELL in neutrophils in severe COVID-19 cases compared to a healthy group, consistent with our observations in the mouse model. These findings suggest that pulmonary perfusion defects caused by neutrophil adhesion to pulmonary vessels contribute to COVID-19 severity.